2016
DOI: 10.1016/j.joco.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of Interactive Binocular Treatment system in amblyopia therapy

Abstract: PurposeTo determine the role of Interactive Binocular Treatment (I-BiT™) as a complementary method of patching in amblyopia therapy.MethodsIn this randomized clinical trial study, 50 unilateral amblyopic children (25 male/25 female) between 3 and 10 years with either best corrected visual acuity (BCVA) ≤20/30 in the amblyopic eye or a difference of BCVA ≥ 2 lines between the two eyes were included. They were randomly classified into the case and control groups (25 in each). Patching was recommended in both gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 19 publications
4
29
0
1
Order By: Relevance
“…Rajavi et al 24 evaluated the addition of I-BiT to patching, and the 4-week posttreatment cessation period that included patching treatment for both groups revealed further improvement of the patients originally randomized to patching (a mean improvement of À0.08AE0.09 logMAR, P ¼ 0.003) only, but no improvement in the group originally randomized to I-BiT plus patching (a mean improvement of À0.01AE0.07 log-MAR, P > 0.99). 24 At the end of the washout/patching period, there was no significant difference in the VA between the 2 groups (0.16AE0.15 vs. 0.18AE0.19 logMAR for the iBiT and control groups, respectively; P ¼ 0.246).…”
Section: Persistence Of Visual Acuity Changes After Treatment Cessationmentioning
confidence: 85%
See 1 more Smart Citation
“…Rajavi et al 24 evaluated the addition of I-BiT to patching, and the 4-week posttreatment cessation period that included patching treatment for both groups revealed further improvement of the patients originally randomized to patching (a mean improvement of À0.08AE0.09 logMAR, P ¼ 0.003) only, but no improvement in the group originally randomized to I-BiT plus patching (a mean improvement of À0.01AE0.07 log-MAR, P > 0.99). 24 At the end of the washout/patching period, there was no significant difference in the VA between the 2 groups (0.16AE0.15 vs. 0.18AE0.19 logMAR for the iBiT and control groups, respectively; P ¼ 0.246).…”
Section: Persistence Of Visual Acuity Changes After Treatment Cessationmentioning
confidence: 85%
“…The authors of this study acknowledged that the total treatment time may have been too short to see an effect. Also in 2016, Rajavi et al 24 reported the results of another randomized controlled trial (level I) to evaluate the role of I-BiT therapy as an adjunct to patching. In this study, 50 subjects aged 3 to 10 years were randomized to patching for 2 hours per day with or without the addition of I-BiT 5 times per week in 20-minute sessions for a total of 4 weeks.…”
Section: Amblyopic Eye Visual Acuitymentioning
confidence: 99%
“…There is a wide age range both within and between these studies; some recruited only adults 72 , other cohorts were pediatric 74,77 , and some included adult and pediatric subjects 75 . Statisical analysis is therefore being applied or compared to a cohort of subjects that may be at different stages of visual maturity.…”
Section: Research Supporting Binocular Therapiesmentioning
confidence: 99%
“…El enfoque binocular pretende obtener, a través de la estimulación de ambos ojos, un efecto secundario sobre la agudeza visual, al eliminar la supresión interocular y permitir la fusión (41). Hess y Thompson describen una serie de tratamientos que permiten la participación del ojo dominante en la terapia (41); es el caso de un tratamiento interactivo binocular (figura 2), también llamado iBit System (42)(43)(44). Otra propuesta es el protocolo de aprendizaje perceptual denominado Push-Pull (45) y un enfoque de juego de acción creado por Noah (46).…”
Section: Tratamientounclassified